2021
DOI: 10.3389/fimmu.2021.696491
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Protein PE6 (Rv0335c), a Novel TLR4 Agonist, Evokes an Inflammatory Response and Modulates the Cell Death Pathways in Macrophages to Enhance Intracellular Survival

Abstract: Mycobacterium tuberculosis (M. tb) is an intracellular pathogen that exploits moonlighting functions of its proteins to interfere with host cell functions. PE/PPE proteins utilize host inflammatory signaling and cell death pathways to promote pathogenesis. We report that M. tb PE6 protein (Rv0335c) is a secretory protein effector that interacts with innate immune toll-like receptor TLR4 on the macrophage cell surface and promotes activation of the canonical NFĸB signaling pathway to stimulate secretion of proi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 79 publications
3
39
0
Order By: Relevance
“…PE/PPE proteins have been reported to use the host inflammatory signaling and cell-death pathways to facilitate disease development [33]. It is widely recognized that PE_PGRS [polymorphic GC-rich-sequence (PGRS)] proteins are essential in TB pathogenesis [29,110,111].…”
Section: Unique Protein Family Pe/ppe/pgrs Present On the Mtb Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…PE/PPE proteins have been reported to use the host inflammatory signaling and cell-death pathways to facilitate disease development [33]. It is widely recognized that PE_PGRS [polymorphic GC-rich-sequence (PGRS)] proteins are essential in TB pathogenesis [29,110,111].…”
Section: Unique Protein Family Pe/ppe/pgrs Present On the Mtb Surfacementioning
confidence: 99%
“…The genome of Mtb has been shown to encode a protein family PE/PPE/PGRS, present exclusively in the genus Mycobacterium [29]. The PE/PPE/PGRS proteins influence cellenvelope remodeling, host cell-death pathways and virulence [30], mycobacterial antigenic variation, immune evasion [31], innate immunity, and bacillary survival in Mphs [32,33]. Polymorphisms in the PE/PPE/PGRS protein family may influence different manifestations of TB, among them AI.…”
Section: Introductionmentioning
confidence: 99%
“…Many Mtb proteins, including some PE/PPE proteins, have been shown to induce apoptosis and autophagy via ROS and MAPK signaling in a TLR2-dependent manner ( 12 , 13 , 15 , 23 , 43 50 ). Unlike those observed here for PPE51, these interactions can result in augmented proinflammatory cytokine production and MHC class II antigen presentation ( 45 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, TLR4 plays a role in defense against mycobacterial infection [ 38 ]. Immune cells can be activated by the interaction between TLR4 and Mtb components, such as secretory protein (Rv0335c), lipomannan (LM), HSPs 60, and 65 [ 65 , 102 ]. In a recent study, Thada et al found that TLR4 can bind TLR8 to recognize TLR8 ligands produced by Mtb [ 103 ].…”
Section: Tlr2 Function In Immune Responses To Mycobacterial Infectionmentioning
confidence: 99%